Profiling of Junior College Football Players and Differences between Position Groups - Lockie, Robert G. (Sports (Basel), 2016)
This study profiled junior college football players. Sixty-two subjects completed vertical jump (VJ; height and peak power), standing broad jump (SBJ), 36.58 m sprint, pro-agility shuttle, three-cone drill, and maximal-repetition bench press and front squat. The sample included 2 quarterbacks (QB), 7 running backs (RB), 13 wide receivers (WR), 1 tight end (TE), 18 defensive backs (DB), 8 linebackers (LB), and 13 offensive and defensive linemen (LM). To investigate positional differences, subjects were split into skill (SK; WR, DB), big skill (BSK; QB, RB, TE, LB), and LM groups. A one-way ANOVA determined between-group differences. LM were taller and heavier than SK and BSK players. The SK and BSK groups were faster than LM in the 0–36.58 m sprint, pro-agility shuttle, and three-cone drill (p ≤ 0.009). The SK group had greater VJ height and SBJ distance; LM generated greater VJ peak power (p ≤ 0.022). There were no between-group differences in the strength endurance tests. Compared to Division I data, junior college players were smaller, slower, and performed worse in jump tests. Positional differences in junior college football are typical to that of established research. Junior college players should attempt to increase body mass, and improve speed and lower-body power.